PERAN KEPEMIMPINAN DAN KOMPETENSI TERHADAP ETOS KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN GOWA - Andi Hobby Maruli Hutosoit; Maat Pono; Julius Jilbert (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to determine the influence of the role of leadership and competence on the work ethic of employees at the Regional Secretariat of Gowa Regency. The data analysis method used in this study uses multiple linear regression tests, correlation coefficient tests and coefficients of determination, t tests and f tests. The results of the study show that partially the role of leadership has a significant effect on work ethic. Because the tcount value is 3.286 > table 0.244, the hypothesis is accepted, partially the competency variable has a significant effect on work ethic. Because the tcount value is 4.788 > table 0.244, the hypothesis is accepted. While simultaneously the variables of the role of leadership and competence have a significant effect on work ethic. Because the Fcount value is 52.696 > Ftable 2.36, the hypothesis is accepted.